Odpowiedź :
Odpowiedź:
2x(6x-10)=8x²-20x
-x(4-5y)= - 4x+5xy
x(x-2y²)-2y(xy-3)= x²-2xy²-2y²x+6
(x-2y)-(y-3)= x-2y-y-3x=-2x-3x
5 nie umiem, mam nadzieję że te obliczenia wyżej są dobrze:)
Odpowiedź:
1. 2x (6x - 10) *musimy pomnożyć nawias przez 2x* = 12x² - 20x
2. -x (4 - 5y) = -4x + 5xy
3. x(x - 2y²) - 2y(xy - 3) = x² - 2xy² - 2xy² + 6y = x² - 4xy² + 6y
4. (x - 2y) - (y - 3x) = x - 2y - y - 3x = -2x - 3y
5. (-2a) x 5 x (-b) + a x 7ab - 2b x (-3a) x 2a = 10abx + 7a²b + 12a²b = 10abx + 19a²b
Szczegółowe wyjaśnienie: